IMPROVING ESP STUDENT’S WRITING SKILL BY USING WRITING ESSAY MODEL - Ina Rohiyatussakinah; Fadilla Oktaviana (FKIP, Universitas Banten Jaya, 2018)
Writing as productive skill is closed with learner in university. They should do lots of writing. English for Academic Purposes programme such as English for Environmental Engineering can be involved in keeping issue logs which are kind of project work. This research investigated of using essay in teaching English as media to improve students’ writing skill. The writer conducted a classroom action research as a method in this research. Writer used Essay as media that was implemented in Environmental engineering class at Banten Jaya University. The class consisted of 25 students. This research was conducted in two cycles. Before doing the treatment, writer gave students pre-test. The mean score of students’ pre test was 65. It indicates that their writing was low. After that, the writer implemented the treatment and gave students post-test. The result of test in cycle one shows that there was improvement, the score was 75. It indicates that there was an improvement from pre-test and post-test one. But, it is still not maximal. Thus, the writer conducted the next cycle (cycle two) in order to reach the target that the students could reach score 80. The result of test in cycle two (post-test two) shows that mean score of students writing was 85. Thus, the using Essay model in teaching writing is excellent to improve students’ writing skill. They was able to gathering ideas, organising the ideas and make essay paragraph with varieties topic that related on their field.